Potential determinants of salinity tolerance in rice (Oryza sativa L.) and modulation of tolerance by exogenous ascorbic acid application - Rahman, Md. Musfiqur; Jahan, Israt; Al Noor, Md. Mahmud; Tuzzohora, Mst. Fatema; Sohag, Abdullah Al Mamun; Raffi, Sharif-Ar; Islam, Mirza Moffazzal; Burritt, David J.; Hossain, Mohammad Anwar (Journal of Phytology, 2020)
Rice is a relatively salt-sensitive crop with the reproductive and seedling stages being the most sensitive. Two separate experiments were conducted to isolate potential determinants of salinity tolerance and to investigate the possibility of modulating salt tolerance by exogenous ascorbic acid (AsA) application. Rice plants were imposed to salinity (EC= 10.0 dS m-1) both at the seedling and reproductive phases of growth. Salinity at the seedling stage resulted a sharp decline in shoot and root growth related traits including leaf chlorophyll content, while hydrogen peroxide (H2O2) and malondialdehyde (MDA) levels increased. Plants experienced with salinity at the reproductive phases of growth showed a significant reduction in yield attributing traits while the tissue levels of H2O2 increased. Exogenous AsA application reversed the negative impact of salt stress, modulating the root and shoots growth and yield related traits and lowering H2O2 and MDA levels. FL-478 was identified as the most tolerant genotype at the seedling stage, with Binadhan-10 being the most tolerant at the reproductive stage. Grain yield panicle-1 significantly and positively corrected with number of filled grains panicle-1, panicle length, plant height, and spikelet fertility, and negatively correlated with H2O2 levels. Stress tolerance indices clearly separated the tolerant and susceptible genotypes. A principal component analysis revealed that the first two components explained 87% of the total variation among the genotypes. Breeding efforts could therefore to undertake for developing salinity tolerance by manipulating endogenous AsA content in rice.